ChemInform Abstract: Visible‐Light‐Promoted Syntheses of β‐Keto Sulfones from Alkynes and Sulfonylhydrazides. Issue 37 (August 2016) - Cai, Shunyou; Chen, Danling; Xu, Yaohui; Weng, Wen; Li, Lihuang; Zhang, Ruijie; Huang, Mingqiang
Abstract: The reaction tolerates various functional groups.